2018
DOI: 10.1016/j.pec.2018.03.014
|View full text |Cite
|
Sign up to set email alerts
|

An expanded framework to define and measure shared decision-making in dialogue: A ‘top-down’ and ‘bottom-up’ approach

Abstract: This SDM framework allows for a more expansive understanding and analysis of how decision making takes place in clinical encounters, including new domains and behaviors not present in existing measures. We hope that this new framework will bring attention to a broader conception of SDM and allow researchers to further explore the new domains and behaviors identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 26 publications
(28 reference statements)
0
31
0
Order By: Relevance
“…However, our approach demands more of research than just a focus on patients’ propositions. For areas of clinical practice that need to be both empirically informed and ethically justified, “top‐down,” deductive research needs to be balanced by inductive “bottom‐up” research; that is, by careful analysis of the ways in which practitioners and patients navigate the demands, constraints and opportunities of specific settings . Such research exposes practices to researchers, theorists, practitioners and educators, who can examine and critique them from different theoretical and ethical perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…However, our approach demands more of research than just a focus on patients’ propositions. For areas of clinical practice that need to be both empirically informed and ethically justified, “top‐down,” deductive research needs to be balanced by inductive “bottom‐up” research; that is, by careful analysis of the ways in which practitioners and patients navigate the demands, constraints and opportunities of specific settings . Such research exposes practices to researchers, theorists, practitioners and educators, who can examine and critique them from different theoretical and ethical perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…Our research directly evaluating live patient consultations indicates that parents express concerns in <40% of encounters, and that clinicians rarely directly ask about parent concerns or fears during consultations for tonsillectomy. 30 Moreover clinicians may neglect to discuss aspects of surgery important to parents, such as anesthesia, and have a tendency towards authoritativeness 36,37 . Research has demonstrated communication pitfalls, such as clinician tendencies to be verbally dominant, ask few open-ended questions, and often neglect to respond to patient fears with direct empathy 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…However, parent concerns are often not shared with, or made clear to, the clinician during surgical consultation. 11 Posts about tonsillectomy on social media outlets provide insight into parental perspectives that may not be expressed to clinicians or researchers. Such social media sources may assist in evaluating patient-centered outcomes related to health care.…”
Section: Introductionmentioning
confidence: 99%
“…5 More recent models of "true" shared decision-making include additional potential domains, including socioemotional support, understandability of clinician dialogue, and recommendation giving. 6 CMS focused on Option Talk, presumably because Option and Decision Talk are harder to document and providing as much information as possible makes common sense. They require that multiple facts regarding the harms and benefits be presented to patients during an in-person shared decision-making visit.…”
Section: Patient-centered Communication and Shared Decision-makingmentioning
confidence: 99%